Penggunaan Metode Problem Based Learning Bagi Siswa Prodi Akuntansi dan Keuangan Lembaga SMK - Rini Ratnaningsih (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this study was to determine the PBL learning process at Attaqwa 05 Kebalen Vocational School, Bekasi district, West Java and to determine the effectiveness of the PBL method on accounting credit debit material at Attaqwa 05 Kebalen Vocational High School, Bekasi district, West Java. The method used in this research is a class action research method (CAR). This method consists of pre-cycle stages, cycle 1 and cycle 2. Data collection was carried out by conducting an initial test on the pre-cycle. The second and third tests were carried out after cycles 1 and 2. The test was in the form of a written test, multiple choice of 30 questions. In addition, interviews and documentation were conducted. The result of this research is that the average value of cycle 1 reaches 72.9. The average value of the cycle reached 73.9. This value concludes that there is an increase in accounting learning outcomes on credit debit material for vocational students. Students have a strong desire to be able to improve scores that are still lacking.